Novinarsko opredeljevanje in razumevanje sovražnega govora - Erjavec, Karmen (Teorija in praksa, 2012)
Due to the absence of studies in the literature to reveal how journalists define and understand hate speech and differentiate it from offensive speech, this research tries to at least partially fill the research gap. Quantitative (content analysis) and qualitative (critical discourse analysis) analyses of interviews with journalists from the main Slovenian media establishments showed that more than one-third of the interviewees cannot define hate speech,while the others can distinguish hate speech and offensive speech. The research also showed that the interviewees have an extremely negative view of hate speech and largely connect it with hostility and violence
Keywords: Hate speech; Sovražni govor; Journalism; Novinarstvo; Svoboda govora; Freedom of speech; Analiza vsebine; Content analysis (Communication); Slovenia; Slovenija